Getting better all the time - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Farmers face multiple problems: food security, land availability, income generation and sometimes the need to understand national agricultural policies. These are the farmers that extension workers are having to meet more and more. But if...